A Roadmap for the Integration of Active Solar Systems into Buildings - Vassiliades, Constantinos; Kalogirou, Soteris A.; Michael, Aimilios; Savvides, Andreas L. (My University, 2019)
This paper aims to simplify the interdisciplinary design process that will be used as a design tool for the viable integration of active solar energy systems into buildings, i.e., Building-Integrated Solar Thermal Systems—BISTSs; Building-Integrated Photovoltaic Systems—BIPVSs, through the creation of a roadmap. The research also aims supplement the work of researchers who have dealt with the creation of design tools that aim to optimise a specific aspect of a building design, or their geometric forms, in order to shape energy-efficient and sustainable architectural solutions. More specifically, a prescriptive design strategy is derived from the proposed design tool. This is based on five design steps, each of which is analysed and which lead to the creation of a comprehensive design tool for siting buildings so as to optimise the integration of solar systems. The originality of this tool is based on the fact that it makes an important step in the standardisation of these studies.
Keywords: Design guidelines; Building integration; Roadmap; Sustainable development; Active solar systems